Answer:
q(x)= 2x+5
r(x)=6
b(x)=x+4
Explanation:
I have found what is missing in your question: Rewrite 2x^2+13x+26/x+4 in the form q(x)+r(x)/b(x).
First, we have to divide the polynomial by x+4 and remember that is x times 2x.
By multiplying this we are going to get
and now we are doing separation of it and getting
and getting
Because 5 is showing x times 5 we are going to multiply (x + 4) with 5 and that is 5x + 20.
![5x+26/x+4 = 5x + 20/x+4 = 6/ x+4=5 + 6/x+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wmhmo9qu5nozo4gsh8iiebsoj0myyrtn4o.png)
Now when we can get more simplified we are having:
![2x^(2) +13+26/x+4=2x + 5= 6/x+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oxilngy836h86imv7gsshloypseahr8tlk.png)